Organo-photoredox catalyzed defluoroacetalation of α-trifluoromethyl alkenes for synthesis of masked γ, γ-difluoroallylic aldehydes. Issue 39 (24th September 2020) - Xiang, Pan; He, Linying; Li, Hao; Qi, Zhongyu; Zhang, Min; Fu, Qiang; Wei, Jun; Du, Xi; Yi, Dong; Wei, Siping
Graphical abstract: Highlights: Organo-photoredox catalyzed defluoroacetalation of α -trifluoromethyl alkenes. The easily accessible glyoxylic acid acetal was the formyl-radical equivalent. The protocol could enable access to masked γ, γ -difluoroallylic aldehydes/ketones. Capable of late-stage functionalization and versatile derivatization. Abstract: An organo-photoredox catalyzed defluoroacetalation of α -trifluoromethyl alkenes with easily accessible glyoxylic acid acetal being the formyl-radical equivalent has been achieved, affording a great variety of masked γ, γ -difluoroallylic aldehydes with good yields and varied functionality tolerance. This mild and transition-metal-free protocol not only allows the incorporation of both an acetal functionality and gem -difluoroalkene moiety into one molecule in a single catalytic cycle, but also offers a straightforward access to masked γ, γ -difluoroallylic ketones. Furthermore, the applicability of the proposed protocol is demonstrated by the late-stage functionalization of biologically active molecules and versatile derivatization of newly generated products.